PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA, DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH THE EFFECT OF GOVERNMENT INTERNAL CONTROL SYSTEM, HUMAN RESOURCE COMPETENCY, AND ACCOUNTIN - Theophilia Fina Febrione Leiwakabessy (Universitas Djuanda Bogor, 2020)
This was study aimed to examined the effect of government internal control systems, human resource competencies and the use of accounting information systems on the quality of Local Government Financial Statements. The population of this research are government officer in Kabupaten Maluku Barat Daya. Sampling was conducted using a judgment sampling method and number of samples are 44 respondents. Technique of data collection is survey by using questionnaires. Analysis using multiple regression analysis. The results showed that human resource competence had a positive and significant effect on the quality of local government financial statements. While the government's internal control system and the use of accounting information systems do not significantly affect the quality of local government financial statements.Keywords: Accounting information systems, Government internal control systems, human resource competencies, local government financial statements